Effect of Different Inflow Cutoff Ratio on Irrigation Water Saving, Yield, WUE and Economics of Wheat Cultivation - Kumar, Jeetendra; Paswan, A.K.; Hasan, Wajid; Rani, Shobha; Kumar, Vijay; Sohane, R.K. (Indian Journal of Extension Education, 2020)
A field experiment was undertaken at farmer’s field to assess different inflow cut off ratio approach for effectivemanagement of irrigation water in wheat and to see its effect on water saving, yield, water use efficiency (WUE) as well as economics. The experiment was laid out with three technological options in which three irrigation were applied by making 5 m wide border strips. Inflow was cut off when advance (wetting) water front reached to 85 percent and 90 percent of border length, respectively in two different technological options whereas infarmer’s practice plots, irrigation was allowed till water stagnation in the field for several hours. It was observed that the practice of water stagnation in the wheat field for several hour was not necessary for optimum productionand water use can be lowered up to 22.93 per cent without yield reduction if irrigation is stopped at 90 percent cut off ratio whereas 27.10 per cent irrigation water saving with slightly reduced yield can be achieved byirrigation using 85 per cent cut off ratio. Therefore, the technological option with inflow cut off ratio of 90 percent was found to be overall efficient followed by 85 percent cut off ratio and it can be successfully used forirrigation management in wheat crop for south Bihar region.